Konsep Pengembangan Desa Wisata Pesisir Tangguh Bencana Berbasis Perencanaan Ruang [Studi Kasus: Desa Kunjir, Kabupaten Lampung Selatan] - Citra Persada; Fadhilah Rusmiati; Nugroho Ifadianto; M.M. Hizbullah Sesunan (Department of Urban and Regional Planning, Diponegoro University, 2022)
Kunjir Village, Rajabasa District, South Lampung Regency, Lampung is a coastal area close to Mount Anak Krakatau (GAK) with potential for catastrophic eruptions, tectonic earthquakes, and tsunamis. On the other hand, Kunjir Village has various marine tourism destinations that have developed in the last 10 years and tourism is one of the sources of community income. In December 2018, Kunjir Village was devastated by the tsunami, therefore it is necessary to improve various aspects, both physical, social, and economic so that Kunjir Village can become a disaster-resilient tourist village. This study aims to develop the concept of developing a Disaster-Resilient Coastal Tourism Village from the physical aspect, which is based on spatial planning. The research method is descriptive qualitative. Primary data collection is obtained from field observations, and interviews, while secondary data is from related agency documents. This research consists of three stages: first, examining the current physical condition of Kunjir Village as a disaster-resilient tourism village; second, develop a strategy for developing Kunjir Village as a Disaster-Resilient tourism village; and third, preparing a zoning plan for the Disaster-Resilient Coastal Tourism Village. The results of the research are the physical condition of the village, spatial planning-based village development strategies and disaster-resilient village zoning. The zoning of Kunjir Village as a Disaster Resilient Village was developed in four zones, namely: as a Buffer Zone or protected area (Zone 1), Aquatic Zone (Zone 2) for ecological conservation and fisheries, Low Density Zone (Zone 3) as coastal culture, tourism and tourism agriculture. Finally, the Tangguh Constructed Zone (Zone 4) for evacuation locations and geopark tourism.